Why human olfaction should not be modeled on theories and tasks of vision - Møller, Per; Köster, Egon P. (Frontiers in Psychology, 2023)
In this paper we analyze some key concepts and problems in olfaction and argue that many concepts borrowed from vision are not helpful in elucidating the functions of human olfaction. This is illustrated with several examples. Olfaction is rarely in the focus of human attention. Olfaction is, compared to vision, a 'hidden sense', but still guides many important behaviors by way of unattended unconscious olfactory perception and implicit memory. Not all olfactory processing, however, is of an unconscious nature. Flavors, and the pleasures gained from them, are most often consciously perceived. These are experiences mostly determined by olfaction, taste, touch and chemesthesis. Different approaches to olfaction have recently been proposed. We discuss two of them, which differ in their inspiration from vision. OurThe analyseis leads us to conclude that olfaction should not be modelled on vision, neither conceptually nor with respect to the problems solved by the two senses. A critical examination of the ecological and physical constraints of olfaction and the other senses should be given priority. Such analyses will further our understanding of which problems are solved by the different senses and how they collaborate to guide us through the world.Humans are endowed with several senses which Gibson (1966Gibson ( , 1979) ) suggested have developed to allow us to interact appropriately with the world we live in. According to Gibson, the different challenges we encounter and the different needs we have require different sensory systems. Unfortunately, most human olfactory studies have not considered ecological or physical constraints of the environment. Nor is it commonplace to analyze the tasks and problems olfaction solve. Why formaterede: Engelsk (USA)